Double Trouble: Challenges in the Diagnosis and Management of Ocular Syphilis in HIV-infected Individuals. (2nd October 2020) - Queiroz, Rafael de Pinho; Smit, Derrick P.; Peters, Remco P.H.; Vasconcelos-Santos, Daniel Vitor
ABSTRACT: Syphilis and HIV infection may coexist in the same individual. Ocular syphilis and/or neurosyphilis may develop at any stage of coinfection, with a stronger association between ocular and neurosyphilis in individuals living with HIV, than in HIV-uninfected individuals. The diagnosis of ocular syphilis in HIV-infected and -uninfected patients remains with some controversy due to unspecific clinical manifestations and limited diagnostic tests. Penicillin is the mainstay of treatment of ocular syphilis, but alternative options are warranted. This review describes the epidemiology, pathophysiology, and clinical manifestations, as well as the diagnostic and therapeutic challenges posed by ocular syphilis against the background of HIV coinfection.